2019
DOI: 10.1039/c9ra05843e
|View full text |Cite
|
Sign up to set email alerts
|

Tannic acid-based nanopesticides coating with highly improved foliage adhesion to enhance foliar retention

Abstract: Poor utilization of conventional pesticides has resulted in overuse, which increases cost, toxicity to other non-target organisms, concerns about human health and safety, groundwater and contamination, with ecosystem destruction and food pollution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…The recorded LC 50 for peach aphid Myzus persicae Sulzer (Hemiptera: Aphididae) were 1.5 mg/L [41], and that was 5.5 mg/L for Anjum et al's bioassay [42]. But results of our study could get support from our recent bioassay on M. persicae (LC 50 of 17.38 mg/L and 10.68 mg/L for Abam-PLA-NS and Abam-PLA-Tanning-NS respctively) [32].…”
Section: Insecticidal Effect Of Nano-formulated Abamectin On the Aphisupporting
confidence: 43%
See 2 more Smart Citations
“…The recorded LC 50 for peach aphid Myzus persicae Sulzer (Hemiptera: Aphididae) were 1.5 mg/L [41], and that was 5.5 mg/L for Anjum et al's bioassay [42]. But results of our study could get support from our recent bioassay on M. persicae (LC 50 of 17.38 mg/L and 10.68 mg/L for Abam-PLA-NS and Abam-PLA-Tanning-NS respctively) [32].…”
Section: Insecticidal Effect Of Nano-formulated Abamectin On the Aphisupporting
confidence: 43%
“…PLA-based nano-formulated abamectin was synthesized according to a previously reported emulsion solvent evaporation method (O/W) [32]. PLA (40 mg/mL) and abamectin (40 mg/ mL) were dissolved in CH 2 Cl 2 by magnetic stirring to form an organic phase.…”
Section: Preparation Of Nano-formulated Abamectinmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface of the nanopesticide could be modified by affinity groups to improve folia adhesion, and the retention rate of the prepared nanopesticide was enhanced by > 50%. 56 Whether SPc can be applied as a common adjuvant is an interesting question. Our previous study confirmed that addition of SPc could improve not only the contact toxicity of matrine against green peach aphids in the laboratory, but also the control efficacy and persistence of matrine, D-limonene and pyrethrin against western flower thrips in the greenhouse.…”
Section: Discussionmentioning
confidence: 99%
“…applied polyethylene glycol‐coated nanoparticles to garlic essential oil to control adult Tribolium castaneum , and the control efficacy increased to over 80% after 5 months due to the slow and persistent release of AIs. The surface of the nanopesticide could be modified by affinity groups to improve folia adhesion, and the retention rate of the prepared nanopesticide was enhanced by > 50% 56 …”
Section: Discussionmentioning
confidence: 99%